Analisis Rasio Profitabilitas sebagai Indikator Pertumbuhan Laba Sebelum dan Selama Invasi Rusia terhadap Ukraina pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Kurnia Sari, Salisma; Desitama, Faizal Satria (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The Russia-Ukraine conflict has had an impact on the global financial system, including Indonesia. The main impact of the Russian-Ukrainian invasion on the global economy is rising energy costs and falling confidence in financial markets. Global inflation will increase due to rising energy costs, which will hinder global economic recovery. By using profitability ratios such as GPM, NPM, ROA, and ROE, the purpose of this study is to find out whether there are differences in profit growth before or during the Russian invasion of Ukraine. The non-probability sampling research sample consists of four banking companies with State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange. This study uses secondary data found in the annual reports on the IDX website for banking companies in 2021 and 2022. Different test analysis (Paired Sample T-Test) was used to analyze the data. This method is used to determine whether there are differences in profit growth calculated by GPM, NPM, ROA, ROE. This study shows that the ratios of GPM, NPM, ROA, and ROE before and during the Russian-Ukrainian invasion have a significant difference in value, namely an increase in all profitability ratios. Keywords: Russian Invasion of Ukraine, Profit Growth, Profitability Ratios